(untitled) (Sains Humanika, 2021)
This study was conducted to identify the relationship between job reward and employee engagement in the organizational context in a supermarket. This quantitative study involved a total of 70 respondents and the data was obtained through the distribution of questionnaire. The analysis was conducted by using Statistical Package of Social Sciences (SPSS) version 22.0. In addition, descriptive analysis involving mean and percentage scores were used to identify levels of reward (intrinsic and extrinsic) as well as employee engagement. The relationship between job reward and employee engagement has been analyzed by using inferential analysis through Pearson correlation. The results show that the level of job reward is moderate, while employee engagement is high. The findings also show that there is a positive relationship between work reward and employee engagement as well as at moderate level. Besides, researcher has provided several suggestions to organization in order to identify and emphasize rewards as an effort to enhance employee engagement.